Developing Sustainable Procurement System Based on Enterprise Resource Planning - Icca Mita Monica; Ari Yanuar Ridwan; Umar Yunan K.S. Hediyanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Seeing the increasing competition in the manufacturing industry, the implementation of Sustainable Supply Chain Management (SSCM) can be a solution to improve the efficiency of a company's supply chain and also increase competitiveness with competitors. PT. Elco Indonesia Sejahtera is a company engaged in the leather tanning industry located in Garut, West Java. This company does not yet have a system to support the implementation of Sustainable Supply Chain Management in its business processes, including for the procurement department. In addition, the company also does not have a system to monitor its business processes. Therefore, this study aims to design an integrated information system for the procurement department using a system based on Enterprise Resource Planning (ERP), as well as to design a monitoring dashboard so that business processes can be more effective, efficient, and of course, able to manage SSCM well. The results of this study are in the form of a system design and a monitoring dashboard based on ERP to support the implementation of SSCM.